If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18k-9=9(2k-1)
We move all terms to the left:
18k-9-(9(2k-1))=0
We calculate terms in parentheses: -(9(2k-1)), so:We get rid of parentheses
9(2k-1)
We multiply parentheses
18k-9
Back to the equation:
-(18k-9)
18k-18k+9-9=0
We add all the numbers together, and all the variables
=0
k=0/1
k=0
| -11-y=33 | | n3=-64 | | 4(-4-7x)+x=-124 | | -11g-18=2-20-11g | | x+x+2+3x-6=31 | | 12.2+2.8w−8.8=1.05w | | 4(2x+8)−6=6x+2(x+13) | | 15.29=3.4897x | | -10(2x+15)=5x | | -12-8z=1-14z+11 | | x^2-2x+6=6x-16 | | 32+8x=-4(4-5x) | | 4(5-n)=7n-4(3n-4) | | 12.3452=w-35 | | t/8=72 | | 2c-18=-2(-c+9) | | v-3.7629=25.3165 | | 2(c-1)-4=8 | | 3(x-3)+4=16 | | 5.50x=17+2.50x | | t/8=70 | | 4+5-10m=-10m+9 | | 2x^2+11=-25 | | 8x+16=52.8 | | 5^(2x+3)-4=21 | | 10(2x-5)=5x | | 3n²+1=37 | | 2(-h+9)=-2h+18 | | 3x-10=-90+x+20/ | | Y=900x/10+45x | | 7x−5=4x−14 | | 3x-10=90+x+20 |